Complete genome sequence of Halomonas sp. Strain SH5A2, a dye-degrading halotolerant bacterium isolated from the salinas and aguada blanca national reserve in Peru - Manya W.F. (2021)
Halomonas sp. strain SH5A2 is a halotolerant bacterium isolated from Salinas Lake at 4,300 m above sea level in Peru. Here, we report its complete genome sequence with a length of 3,849,224bp and highlight the presence of genes putatively related to dye degradation, such as NADPH-dependent oxidoreductases. © 2021 Manya et al. This is an open-access article distributed under the terms of the Creative Commons Attribution 4.0 International license.